Psychological Well-being and Digital Intervention in Youngster’s - An Overview - Agrawal, Shraddha; Suvidha, (International Journal of Scientific Research in Science and Technology, 2024)
This study evaluates and reviews the literature to point out and ascertain the state of mental health and the impact of mental health intervention initiatives on youngster’s psychological well-being. It also throws light on importance of technology in our day-to-day life. Digital technology plays a very important role and offers expanded access to evidence-based interventions. This is a certain fact that many mental health issues and concerns in youngsters may be treated with evidence-based therapies, but the matter of fact is that there are not plenty of options available. Therefore, to ensure the use of technology for mental wellbeing interventions this work was taken up.
Keywords: Intervention programme; Youngsters; Psychological Well-Being; Mental Health